THE EFFECT OF VARIABLE MICROWAVE-POWER ON THE LOW-FIELD ABSORPTION IN HIGH-TC SUPERCONDUCTING CUPRATES - Janes, R; Liu, R; Edwards, P; Tallon, J (1990)
The well established low-field microwave absorption below Tc has been investigated using the ESR technique at 9 GHz, as a function of incident microwave power, in a range of superconducting cuprates, namely Er2Ba4Cu7O15-x, Tl2Ba2CeCu2Ox and YBa2Cu3O7-x. In all cases, the signal was 'saturated' above a critical microwave power level; we observed that this effect was sample-dependent.